The Politicisation of the European Union and the Role of the European Parliament: Opportunities, Risks and Limitations - Warasin, Markus (Journal of Management Policy and Practice, 2020)
Politicisation of the EU has become an important subject in debates about the future of the European governance. This paper addresses the distinguished and unprecedented politicisation-push that the EU has been experiencing through the emergence of sovereignty, identity and solidarity conflicts in the context of the poly-crises - from negative referenda outcomes to the global financial and economic crisis as well as against the backdrop of the migration crisis. Politicisation is heavily influencing and substantially re-shaping the EU institutions and the EU-level Civil Society. After theoretically outlining the concepts of constructive vs. destructive politicisation, the paper focusses on the political dynamics in the women’s rights committee of the European Parliament as a highly politicised arena. The chapter addresses in particular the gender specific cooperation and alliances between and within political groups and party federations by analysing the key factors which influence decision-making in the context of the EP, both at plenary and committee level: distribution of seats among political groups, intra-group cohesion and inter-group coalitions.